1974
DOI: 10.1073/pnas.71.7.2813
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical Model for Human Population

Abstract: We analyze a simple, deterministic model of the dynamics of population changes in a bisexual, reproductive system based on marriage. Our model is one of a general class, special cases of which have been previously discussed within the framework of population biology by D. G. Kendall, L. A. Goodman, J. H. Pollard, and others. Here, we extend and complete previous analyses of systems characterized by first-degree homogeneous, unbounded marriage functions, allowing for arbitrary birth and death rates.The dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…[12] As is well known, Kendall (14), Goodman (8,15), and Yellin and Samuelson (16), and as Fisher does not fail to notice, the additive form for the biparental birth function of Eq. 11 has the unrealistic property that increasing the numbers of one sex alone adds unflaggingly to the birth rate.…”
mentioning
confidence: 99%
“…[12] As is well known, Kendall (14), Goodman (8,15), and Yellin and Samuelson (16), and as Fisher does not fail to notice, the additive form for the biparental birth function of Eq. 11 has the unrealistic property that increasing the numbers of one sex alone adds unflaggingly to the birth rate.…”
mentioning
confidence: 99%
“…Many commonly used mating functions are generalized weighted means (Hölder means) of the form where and are constants; 0 ≤ ≤ 1 , < 0 (Hadeler 1989;Bessa-Gomes et al 2010;Iannelli et al 2005). Figure 1 shows several generalized weighted mean mating functions and biologically desirable criteria that they satisfy (McFarland 1972;Pollard 1974;Yellin and Samuelson 1974).…”
Section: Modeling the Mating Processmentioning
confidence: 99%
“…used this technique to investigate the qualitative behavior of a general two-sex model of the Kendall type. They added a break-up rate for pairs with a general pair-formation law, and showed that if the mortalities of males and females do not differ very much there is a globally attractive two-sex exponential solution with constant sex ratio (see also Yellin and Samuelson (1974)). Instead of birth rates ~epending linearly on the number of pairs, one can also consider a constant recruitment rate 1C in ~emographic models:…”
Section: ··-mentioning
confidence: 99%